Antidiabetic drugs use and new-onset atrial fibrillation in patients with diabetes mellitus. (14th October 2021) - Fauchier, L; Fauchier, G; Bisson, A; Bodin, A; Herbert, J; Angoulvant, D; Ducluzeau, P.H; Lip, G.Y.H
Abstract: Background: Diabetes is one of the most common chronic disorders worldwide and is an important cause of cardiovascular disease. Large studies investigating the risk of atrial fibrillation (AF) in diabetic patients taking different diabetes medications are still missing. Methods: The analysis was based on the EGB ("Echantillon Généraliste des Bénéficiaires") database, a 1/97 representative sample of the French nationwide claims and hospitalisation database. A cohort comprising 25, 117 adult patients with diabetes and no previous AF seen between 2010 and 2018 was created and followed until December 2018 for incidence of new-onset AF. Among these diabetic patients, 36.0% were treated with metformin, 32.0% were treated with Sulfonylureas, 7.0% were treated with DPP4-inhibitors, 1.6% were treated with GLP1- analogues and 19.6% were treated with insulin. A Cox proportional hazards model was used to determine factors and different oral diabetes medications independently associated with the risk of AF during follow-up. Results: During a follow-up of 4.8±3.5 years, there were 3, 300 patients with new onset AF (yearly rate 2.7%). In multivariable analysis, among baseline characteristics, we found that older age, male sex, hypertension, heart failure, aortic stenosis, chronic kidney disease, anemia and diuretic use were independently associated with a higher risk of new AF. Among diabetes medications included in the multivariable model, use of sulfonylureas was independently associated with a lower risk of AF (HR 0.86, 95% CI 0.80–0.92, p<0.0001 vs no use). By contrast, use of GLP1-analogues (HR 2.27, 95% CI 1.49–3.46, p=0.0001 vs no use), DPP4-inhibitors (HR 1.88, 95% CI 1.59–2.22, p<0.0001 vs no use), metformin (HR 1.09, 95% CI 1.01–1.18, p=0.03 vs no use) and of insulin (HR 1.15, 95% CI 1.05–1.26, p=0.004 vs no use) were independently associated with a higher risk of AF. Conclusions: Patients with different diabetes medications have significantly different long-term risk of AF. Specifically, sulfonylureas use was associated with a lower risk of incident AF whilst other antidiabetic drugs were associated with a higher risk of AF during follow-up. Funding Acknowledgement: Type of funding sources: None.